2010
DOI: 10.1016/j.jalgebra.2010.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A universal approach to vertex algebras

Abstract: In this paper, we characterize vertex algebras (in the appropriate sense) as algebras over a certain graded co-operad. We also discuss some applications and categorical ramifications of this characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…We will show only the construction of the map (17) in the case whenΣ is closed (i.e. where the definitions of the two Pfaffian lines are different).…”
Section: Fermions On Compact Surfaces Imentioning
confidence: 99%
“…We will show only the construction of the map (17) in the case whenΣ is closed (i.e. where the definitions of the two Pfaffian lines are different).…”
Section: Fermions On Compact Surfaces Imentioning
confidence: 99%
“…Let F be any field of characteristic 0. We recall from [9] the ordered configuration space C(n) = C(z 1 , ..., z n ) of n distinct points z 1 , ..., z n in A 1 . Denote the coefficient ring of the affine variety C(n) by C(n).…”
Section: The Basic Definitionsmentioning
confidence: 99%
“…It is advantageous to consider C(n) = C(z 1 , ..., z n ) a Z-graded ring with grading by total degree of a homogeneous rational function. In [9], it is shown that the system (C(n)) is a graded co-operad: the comultiplication (…”
Section: The Basic Definitionsmentioning
confidence: 99%
See 2 more Smart Citations